Microeconomics and behavior - Frank, Robert H. (McGraw-Hill Irwin, 2010)
Robert Frank's Microeconomics and Behavior covers the essential topics of microeconomics while exploring the relationship between economic analysis and human behavior. Core analytical tools are embedded in a uniquely diverse collection of examples and applications to illuminate the power and versatility of the economic way of thinking. Students are encouraged to become "Economic Naturalists" who see the mundane details of ordinary existence in a sharp new light. Connect is the only integrated learning system that empowers students by continuously adapting to deliver precisely what they need, when they need it, and how they need it, so that your class time is more engaging and effective